KARAKTERISTIK PEDAGANG KAKI LIMA PADA RUANG PUBLIK (STUDI KASUS: ALUN-ALUN TENGKU AMIR HAMZAH STABAT) - Irsanuddin Luthfi (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2022)
Tengku Amir Hamzah Stabat Square is a public space that accommodates all community activities in Stabat District and itssurroundings. The activities of street vendors who occupied public spaces raise pros and cons. Street vendors not onlyinterfere with the use of public spaces, but also provide social space and are able to attract people to gather and reviveactivities in public spaces. This study aims to reveal the characteristics and space-forming elements applied by streetvendors, due to the absence of studies related to the study of street vendor characteristics. This research is a qualitative andquantitative research with data analysis using descriptive analysis method. Data collection was carried out throughobservation and documentation methods as well as interviews. The results of this study indicate that the profilecharacteristics of street vendors are dominated by the adult age group (26-45 years) who still come from this neighborhoodor live not far from the research location with the last education level being SMA/ SMK (highschool). Street vendors in theresearch area sell food/drinks using carts/pushchairs. The elements that formed a public space applied by street vendorsare elements of comfort and image, access and linkage, uses and activity, and sociability. To create comfort and imageelements, street vendors provide physical attributes such as benches/chairs, tables, shade, games and music. Its strategiclocation due to close proximity to the city's bustling centers really supports the elements of access and linkage. The usesand activities elements offered by traders are places to eat or drink, play, relax, and recreation. Street vendors are able toaccommodate elements of sociability such as enjoy the panoramic view or scenery, meeting friends, interacting with otherpeople, and gathering with family, all of this because the variety of merchandise offered at relatively low price.